2004
DOI: 10.1007/s00192-004-1194-0
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle strength and thickness in continent and incontinent nulliparous pregnant women

Abstract: The aim of the study was to measure pelvic floor muscle function in continent and incontinent nulliparous pregnant women. The study group consisted of 103 nulliparous pregnant women at 20 weeks of pregnancy. Women reporting urinary incontinence once per week or more during the previous month were classified as incontinent. Function was measured by vaginal squeeze pressure (muscle strength) and increment in thickness of the superficial pelvic floor muscles (urogenital diaphragm) assessed by perineal ultrasound.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
100
1
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 28 publications
11
100
1
12
Order By: Relevance
“…Moreover, other studies evaluating vaginal squeeze pressure in continent women reported values in the same area, which compares favourably with values of mixed-race and white women in the present study [18,28]. However, caution must be exercised when direct comparisons are made as measurements have been done with different measuring apparatus [15] Mean maximal contraction values for women with SUI or mixed incontinence have much lower reported values (5-16.2 cmH 2 O) [16,26,26,[29][30][31]. Mixed-race students had the lowest maximal pressure readings (15.6 cmH 2 O) in this study and can be compared to the bottom range of values reported by healthy women and the upper range of values of women with SUI.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, other studies evaluating vaginal squeeze pressure in continent women reported values in the same area, which compares favourably with values of mixed-race and white women in the present study [18,28]. However, caution must be exercised when direct comparisons are made as measurements have been done with different measuring apparatus [15] Mean maximal contraction values for women with SUI or mixed incontinence have much lower reported values (5-16.2 cmH 2 O) [16,26,26,[29][30][31]. Mixed-race students had the lowest maximal pressure readings (15.6 cmH 2 O) in this study and can be compared to the bottom range of values reported by healthy women and the upper range of values of women with SUI.…”
Section: Discussionsupporting
confidence: 75%
“…Esses resultados corroboram outros estudos que demonstraram que os exercícios para o AP podem aumentar a FMP e reduzir a gravidade da IU, tanto em relação à frequência quanto ao volume de perda urinária, ou, até mesmo, curar a incontinência em gestantes 20,21 e não gestantes 13 . Teoricamente, esses resultados podem ser explicados pelo fortalecimento dos músculos do AP e dos músculos periuretrais, que passam a reforçar o mecanismo de continência 22 .…”
Section: Discussionunclassified
“…2) [10,13]. The pubovisceral angle is the line between the vertical line that transverses the urethra and rectum and the tangent line that connects the point where the vertical line crosses the inner edge of the puborectal loop with the most distant inner point of the pubovisceral muscle [20].…”
Section: ) 3-dimensional Ultrasound Measurementsmentioning
confidence: 99%
“…However, recent technological advances in 3D ultrasound have allowed access to the axial plane and direct imaging of the entire levator hiatus, previously the domain of MRI. Several studies have recently defi ned characteristics of the pelvic fl oor following delivery, especially, the effects of delivery mode on the pelvic fl oor [10,11]. However, there is still a lack of studies describing the effects of pregnancy itself on the pelvic fl oor.…”
mentioning
confidence: 99%